Biomass Microcapsules with Stem Cell Encapsulation for Bone Repair - Lei Yang (SpringerOpen, 2021)
Abstract Bone defects caused by trauma, tumor, or osteoarthritis remain challenging due to the lack of effective treatments in clinic. Stem cell transplantation has emerged as an alternative approach for bone repair and attracted widespread attention owing to its excellent biological activities and therapy effect. The attempts to develop this therapeutic approach focus on the generation of effective cell delivery vehicles, since the shortcomings of direct injection of stem cells into target tissues. Here, we developed a novel core-shell microcapsule with a stem cell-laden core and a biomass shell by using all-aqueous phase microfluidic electrospray technology. The designed core-shell microcapsules showed a high cell viability during the culture procedure. In addition, the animal experiments exhibited that stem cell-laden core-shell microcapsules have good biocompatibility and therapeutic effect for bone defects. This study indicated that the core-shell biomass microcapsules generated by microfluidic electrospray have promising potential in tissue engineering and regenerative medicine.